(untitled) (American Journal of Economics and Business Innovation, 2025)
The protracted civil conflict in South Sudan has significantly impeded the development of infrastructure, particularly the road system, which remains inadequate or nonexistent in many rural areas where 80% of the population resides. Among the many difficulties faced by construction companies include material delivery delays, a shortage of local skilled labor, disruptions during the rainy season, insecurity, delayed project approvals and payments, and a large number of public holidays. Furthermore, culturally motivated employee procrastination has a detrimental impact on output. Employee pay usually does not take these difficulties into consideration, which affects business performance. The purpose of this study was to suggest innovative payment strategies suited to the unique construction environment of South Sudan. The study employed a mixed-methods approach. Data was collected from eight project locations via questionnaires, interviews, and workshops. SPSS and qualitative content analysis were used to analyze the data. Three successful pay models were found: Management-Driven Pay (MDP), Shared Pay Rate (SPR), and Team-Based Pay (TBP). These strategies seek to match incentives with actual problems that exist on the ground, such as security and weather. To encourage better labor relations in the industry, the report suggests modifying the Labor Act of 1997.